On the construction of solutions of linear differential equations according to given sequences - Shavala, O. V. (Ukrains’kyi Matematychnyi Zhurnal, 2017)
We consider the problem under what conditions the equation f′ ′ + Af = 0 possesses an entire (meromorphic) solution with given sequences of zeros (poles) and critical points. The results are extended to equations of higher orders.